Zinc in Irrigated Soils of The Desert (Texas Journal of Agriculture and Biological Sciences, 2023)
The research delved into the geochemical and biogeochemical characteristics of hydromorphic soils within the desert area, focusing on the Yazyavan region as a case study. The primary emphasis was on understanding the pedobiogeochemical aspects of Zinc, particularly its accumulation patterns and anomalies. This investigation developed a framework to quantify both positive and negative anomalies.